PENGARUH PERSEPSI SISWA TENTANG KOMPETENSI PROFESIONAL GURU DAN MINAT BELAJAR SISWA TERHADAP PRESTASI BELAJAR SEJARAH SISWA KELAS XI IPS DI SMA NEGERI 3 BOYOLALI TAHUN PELAJARAN 2012-2013 - Pradika, Dimas Fajar (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2013)
Dimas Fajar Pradika K4409019. THE EFFECT OF STUDENT PERCEPTION ABOUT TEACHER?S PROFESSIONAL OF COMPETENCE AND INTEREST LEARNING TO THE HISTORY LEARNING ACHIEVEMENT 11th GRADE STUDENTS OF SMA N 3 BOYOLALI SCHOOL YEAR 2012/2013. Script. Surakarta: Teacher Training and Education. Sebelas Maret University Surakarta, July 2013. The aims of this study were to investigate the effect of: (1) Perception of students about the professional competence of t history learning achievement. (2) Interest in learning the history of history learning achievement. (3) Students 'perceptions about teacher?s professional competence and interest in learning history learning achievement This research used survey method with a correlational design. The samples of research are 57 students from 4 classes of SMA N 3 Boyolali. In taking of the samples used sample proportional cluster random sampling techniques from 117 students in population. The population in this study were students of class XI SMA Negeri 3 IPS Boyolali a sample of 117 students taking 4 classes with as many as 57 students. Sampling technique using tenik Proportionate cluster random sampling (random class groups), The data were collected by using instruments namely documentation and questionnaire in the form of likert scale. The techniques of data analysis were correlation and regression techniques. According to the research, the researcher found: (1) The effect of students' perceptions about teacher?s professional competence of to the history learning achievement of 11th grade students of SMA N 3 Boyolali obtained by calculation the value is its relative contribution 45,% and its effective contribution is 10,89% so the hypothesis as follows